2023
DOI: 10.3389/fphys.2023.1175227
|View full text |Cite
|
Sign up to set email alerts
|

Potential pharmacological mechanisms of four active compounds of Macleaya cordata extract against enteritis based on network pharmacology and molecular docking technology

Abstract: Background:Macleaya cordata extract (MCE) is effective in the treatment of enteritis, but its mechanism has not been fully elucidated. Therefore, this study combined network pharmacology and molecular docking technologies to investigate the potential pharmacological mechanism of MCE in the treatment of enteritis.Methods: The information of active compounds in MCE was accessed through the literature. Furthermore, PubChem, PharmMapper, UniProt, and GeneCards databases were used to analyze the targets of MCE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“… 19 Recent studies have shown that network pharmacology combined with metabolomics (ultra-high performance liquid chromatography and mass spectrometry) or molecular docking can effectively reveal the underlying mechanisms of drug therapy. 20 , 21 For example, researchers found that agarwood intervention can affect the metabolic composition of mice serum, and further combined with network pharmacology to analyze key compounds, targets and biomarkers, clarifying the feasibility of the material basis and mechanism of biomarkers. 22 The components of Xihuang Pills can directly act on the target of androtinib, regulate endogenous metabolic disorders in vivo, and thus synergically inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Recent studies have shown that network pharmacology combined with metabolomics (ultra-high performance liquid chromatography and mass spectrometry) or molecular docking can effectively reveal the underlying mechanisms of drug therapy. 20 , 21 For example, researchers found that agarwood intervention can affect the metabolic composition of mice serum, and further combined with network pharmacology to analyze key compounds, targets and biomarkers, clarifying the feasibility of the material basis and mechanism of biomarkers. 22 The components of Xihuang Pills can directly act on the target of androtinib, regulate endogenous metabolic disorders in vivo, and thus synergically inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%